Regulating land-based sources and activities causing pollution of the coastal and marine environment in South Africa, Kenya and Nigeria within the context of integrated coastal zone management - Kadiri, Temitope Emmanuela (Institute of Marine and Environmental Law, 2016)
Includes bibliographical references